Perishable Product Inventory Model by Considering Expiration Period and Discount Factor - Aritonang, Kinley; Pratiwi, Loren; Ricardo, Cherish; Nainggolan, Marihot; Chandra, Nicholaus Ivan (Archives of Business Research, 2024)
The grocery stores usually sell the deterioration (perishable) products. One example of a deterioration product is 1-liter packaged milk product. Often when approaching or even reaching the expiration date, those products still cannot be sold out but with the discount offered, it is hope that those products will be sold more. It is necessary to determine the time for giving the discount and the discount rate that give the optimal net profit. This study develops a deterioration product inventory model by considering the expiration factor and the discount factor. By providing the required parameter values ​​in the model, a simulation was carried out, and it can be determined the level of inventory, the time of the discount offered, and the amount of the discount offered, which results in an optimal net profit.